Hubungan antara Kepuasan Kerja Pada Aspe Self Esteem Dengan Motivasi Perawat Pelaksana - Endrika Setya Utami; Supratman Supratman (Universitas Muhammadiyah Surakarta, 2020)
Self-esteem is the assessment made by a person against himself. The assessment is usually reflects the acceptance or rejection of him and shows how far people believe that she can be successful, feel important and valuable. To increase the satisfaction of the esteem every aspect of nurses required to have a high motivation to have a good self-satisfaction. As for the purpose of this study is to determine the relationship between satisfaction on aspects of self-esteem and motivation of nurses in hospital Panti Rahayu (Yakkum) Purwodadi. This research is a quantitative data in the form of numbers / figures, with a correlation descriptive research design. The population in this study are all nurses in hospital Panti Rahayu (Yakkum) Purwodadi totaling 136 perawat. Sampel used in this study proportional random samplingyang totaling 62 nurses. Data collection techniques using research instruments such as questionnaires. While data analysis technique used is Rank Spearman using SPSS. The results obtained which showed a significant relationship between satisfaction on aspects of self esteem and motivation nurses working in hospital Panti Rahayu (Yakkum) with sig (2-tailed) 0.001. These results indicate that the presence of nurses who work motivation can increase satisfaction in the aspects of high self esteem in nurses in Panti Rahayu (Yakkum) Purwodadi.